Improvement of phase structure and energy storage properties of [(0.72-x)Bi0.5Na0.5TiO3-0.28SrTiO3-xBaZr0.05Ti0.95O3] lead-free ceramics - Phakakorn Panpho; Navavan Thongmee; Krailas Mathrmool; Muangjai Unruan; Narathip Vitayakorn; Rattiphorn Sumang (Ferroelectrics, 2022)
Lead-free [(0.72-x)Bi0.5Na0.5TiO3-0.28SrTiO3-xBaZr0.05Ti0.95O3] ceramics (abbreviated as BNT-ST-xBZT), x = 0, 0.03, 0.05, 0.07, 0.10, and 0.15 wt.%, were prepared by conventional solid-state reaction method. The effect of x(BZT) content on phase structure, microstructure, dielectric, ferroelectric, and energy storage properties of BNT-BT-x(BST) ceramics was studied. The samples of the study were analyzed through X-ray diffraction (XRD). The XRD patterns were analyzed using Rietveld refinement. The XRD revealed a single-phase perovskite for all the samples with coexisting rhombohedral and tetragonal phases. It shows the increasing of x(BZT) content and, more tetragonal distortion of the phase. The scanning electron micrographs (SEM) of all the samples displayed spherical-like morphology. The grain growth inhibited by increasing of x(BZT) content. The average of grain size decreased from 2.74 µm to 0.65 µm with BZT content. The highest density (ρ = 5.31 ± 0.11 g/cm3), recoverable energy storage density (Wrec = 0.234 J/cm3), and energy storage efficiency (η = 90%) at 30 kV/cm were found in the composition of x(BZT) = 0.05 wt.%.
Keywords: Ferroelectric and Piezoelectric Materials; Microwave Dielectric Ceramics Synthesis; Dielectric materials and actuators